1993
DOI: 10.1007/bf00169256
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by anaesthetics of 14C-guanidinium flux through the voltage-gated sodium channel and the cation channel of the 5-HT3 receptor of N1E-115 neuroblastoma cells

Abstract: The influence of local and general anaesthetics on cation influx through the fast, voltage-dependent sodium channel and the 5-HT3 receptor cation channel was studied in N1E-115 mouse neuroblastoma cells by measuring 2-min influx of the organic cation 14C-guanidinium induced by either veratridine (1 mmol/l) or 5-HT (100 mumol/l). The veratridine-induced influx of 14C-guanidinium was potentiated by scorpion toxin and inhibited by tetrodotoxin. The 5-HT-induced 14C-guanidinium influx was not affected by tetrodoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
0
3

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 45 publications
3
42
0
3
Order By: Relevance
“…This consideration is consistent with a recent electrophysiological study in the human brain cortex that propofol depresses voltage-dependent Na + channels by a reduction of the averaged fraction open time and an interaction with the steady-state activation with a halfmaximal effective concentration (ECso) of 20 gmol/1 (Frenkel and Urban 1991). Using influx measurement of 14C-guanidinium in NIE-115 neuroblastoma cells, Barann et al (1993) also have reported inhibition of voltage-gated Na + channels by propofol with a halfmaximal inhibitory concentration of 30 gmol/1. The precise mechanism, or site of action, of propofol on voltage-dependent Na + channels remains to be determined.…”
Section: Discussionsupporting
confidence: 90%
“…This consideration is consistent with a recent electrophysiological study in the human brain cortex that propofol depresses voltage-dependent Na + channels by a reduction of the averaged fraction open time and an interaction with the steady-state activation with a halfmaximal effective concentration (ECso) of 20 gmol/1 (Frenkel and Urban 1991). Using influx measurement of 14C-guanidinium in NIE-115 neuroblastoma cells, Barann et al (1993) also have reported inhibition of voltage-gated Na + channels by propofol with a halfmaximal inhibitory concentration of 30 gmol/1. The precise mechanism, or site of action, of propofol on voltage-dependent Na + channels remains to be determined.…”
Section: Discussionsupporting
confidence: 90%
“…[14C]Guanidinium was applied as an organic cation which has been shown to be suitable to investigate the cation permeability of voltagedependent sodium channels (Catterall and Nirenberg 1973;Reith 1990;Barann et al 1993) and 5-HT3 receptor channels ( Reiser and Hamprecht 1989;B6nisch et al 1993;Emerit et al 1993;G6thert et al 1995). Under the present conditions, 5-HT alone was rather weakly effective in inducing influx of [14C]guanidinium, but this influx was potentiated by substance P which, given alone, was ineffective.…”
Section: Discussionmentioning
confidence: 74%
“…The investigations of the effects of ifenprodil (present study) and pentobarbital (Barann et al 1997a) are part of a more comprehensive, comparative study of the kinetics of various putative non-competitive antagonists at 5-HT 3 receptors (e.g. general anaesthetics from different chemical classes; Barann et al 1993).…”
Section: Introductionmentioning
confidence: 99%